Effective Learning Strategies in Improving Elementary School Students' Character: A Systematic Literature Review - Junaidi, Junaidi; Rohmani, Rohmani (PT. Riset Press International, 2024)
Character education plays a crucial role in shaping the quality personality of elementary school students. Effective learning strategies have been identified as a key approach to enhancing students' characters through education. These strategies help students understand and internalize the desired character values in their daily lives. This study aims to conduct a systematic literature review on effective learning strategies to enhance the characters of elementary school students. The methodology used is Systematic Literature Review (SLR), the data analysis approach is content analysis, and the database from Google Scholar or Google Scholar in the last three years (2020-2023) is analyzed. The results of this research obtained a database with the keywords